ChatGPT in Language Education: Perceptions of Teachers - A Beneficial Tool or Potential Threat? - Nugraheni Widianingtyas; Thomas Wahyu Prabowo Mukti; Ronald Maraden Parlindungan Silalahi (VELES Voices of English Language Education Society, 2023)
The burgeoning advancement in artificial intelligence, particularly ChatGPT, has increasingly drawn attention among specialists and practitioners. This study investigates the perceptions of language teachers in Indonesia regarding ChatGPT's potential as a language learning tool and the concerns associated with its deployment. A quantitative approach was adopted, utilizing an online questionnaire comprised of 18 items rated on a four-point Likert scale and three open-ended queries. The sample included 100 educators, spanning English, Indonesian, and Mandarin language teachers and lecturers. Findings indicate that a significant proportion of respondents are familiar with internet-based artificial intelligence and recognize the applicability of ChatGPT in pedagogical contexts. Notably, 87% of language educators endorse initiatives to enhance understanding and integration of Artificial Intelligence in Education (AIEd) to bolster instructional efficiency and efficacy. Consequently, a majority concur that ChatGPT can aid language learners in honing vocabulary, grammar, oral and written competencies. Based on these insights, it is imperative for educational stakeholders to strike a judicious equilibrium between the deployment of AI tools and a pedagogical paradigm that emphasizes student engagement and critical cognitive development.